2017
DOI: 10.1038/srep40295
|View full text |Cite
|
Sign up to set email alerts
|

Sox10+ adult stem cells contribute to biomaterial encapsulation and microvascularization

Abstract: Implanted biomaterials and biomedical devices generally induce foreign body reaction and end up with encapsulation by a dense avascular fibrous layer enriched in extracellular matrix. Fibroblasts/myofibroblasts are thought to be the major cell type involved in encapsulation, but it is unclear whether and how stem cells contribute to this process. Here we show, for the first time, that Sox10+ adult stem cells contribute to both encapsulation and microvessel formation. Sox10+ adult stem cells were found sparsely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…35, 1014 In recent years, accumulating studies showed that Sox10+ stem cells exist in multiple adult tissues and participate in tissue remodeling, including spinal cord, 12 inferior turbinate, 22 periodontal ligament, 23 hair follicle, 24, 25 mammary epithelium, 26 bone marrow, 27 blood vessel walls 1921, 28 and subcutaneous loose connective tissues. 29 Moreover, Sox10 also plays a role in tumor formation of melanoma. 30 Lineage tracing and advanced imaging techniques have been widely used to study cell differentiation during development.…”
Section: Discussionmentioning
confidence: 99%
“…35, 1014 In recent years, accumulating studies showed that Sox10+ stem cells exist in multiple adult tissues and participate in tissue remodeling, including spinal cord, 12 inferior turbinate, 22 periodontal ligament, 23 hair follicle, 24, 25 mammary epithelium, 26 bone marrow, 27 blood vessel walls 1921, 28 and subcutaneous loose connective tissues. 29 Moreover, Sox10 also plays a role in tumor formation of melanoma. 30 Lineage tracing and advanced imaging techniques have been widely used to study cell differentiation during development.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we found Sox10 + stem cells in the stroma of subcutaneous connective tissues which had the same properties as MVSCs in large vessels 24 , 25 . These Sox10 + stem cells are precursors of pericytes and fibroblasts, as described in the previous section, and contribute to both fibrosis and microvessel formation during tissue repair and regeneration 24 . Gli1 + stem cells had similarly wide distribution as the Sox10 + stem cells and were found in the perivascular space and also adventitial layer of large arteries.…”
Section: Stem Cells In Vascular Remodelingmentioning
confidence: 71%
“…Notably, most of these foam cells are initially derived from preexisting intimal-resident myeloid progenitors rather than recently recruited blood monocytes 23 . In addition, the inflammatory cells activate medial SMCs and stem cells, prompting adventitial stem cells to proliferate and migrate into the intima, where they may differentiate and also obtain some properties of myofibroblasts and macrophages 3 , 20 - 22 , 24 , 25 . Disease proceeds as the abnormal vascular wall processes prompt macrophages, together with leukocytes, activated ECs, and SMCs, to secrete increasing amounts of inflammatory cytokines to recruit more inflammatory cells from the circulation and resident adventitial tissues.…”
Section: Overview Of Atherosclerotic Vascular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-layered spheroids are obtained through the application of external magnetic fields. [136][137][138][139][140] However, Matrigel is limited to in vitro applications, since it derives from the Engelbreth-Holm-Swarm (EHS) sarcoma. Adapted with permission.…”
Section: Temperature-responsive Cell Encapsulation Systemsmentioning
confidence: 99%